Zapata, colombian orisha (The Voz a Vos Bulletin, 2021)
Reflection about the importance of Manuel Zapata Olivella, one of the founding professors of the Bachelor of Arts Education with an emphasis on dance and theater, in the academic and cultural field of Africa, especially in Colombia, his country of origin. Recognizing his spirit as a free, mestizo, and universal man.
Keywords: Zapata; Orisha; África; Identity